Positive electrode active material, positive electrode containing the same, and lithium secondary battery
By using the composite material represented by chemical formula 1 as the positive electrode active material of lithium-ion batteries, the solid solution phase and composite phase in the composite material are used to solve the problem of battery voltage drop and energy density reduction caused by invertible oxygen redox capacity, and the battery performance with high energy density and long life is achieved.
Patent Information
- Application Number
- JP2024167963
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-09-27
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The positive electrode active materials of existing lithium-ion batteries are not reversible enough due to the inversion of oxygen redox (O-redox) capabilities, resulting in the problem of voltage drop and energy density drop during the charging and discharging process of the battery.
The composite material represented by chemical formula 1 is used as the positive electrode active material, which contains composite oxides of lithium, nickel and manganese. By adjusting the chemical composition and heat treatment conditions, the coexistence of solid-solved phase and composite phase in the composite material is ensured, and the specific weight of the oxygen redox capacity to control the total weight.
The high energy density and long life of the positive electrode active material are achieved. By controlling the proportion of the specific weight of the oxygen redox capacity to the total weight, the voltage drop and energy density reduction of the battery during charging and discharging are avoided.
Smart Images

Figure 2025059073000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material, a positive electrode containing the same, and a lithium secondary battery. [Background technology]
[0002] Lithium secondary batteries, which have high energy density and are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, notebook computers, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage power sources for hybrid and electric vehicles.
[0003] In order to realize a lithium secondary battery suitable for such applications, various positive electrode active materials have been investigated. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, while the demand for large-sized, high-capacity, or high-energy density lithium secondary batteries has recently increased rapidly, the supply of transition metals such as nickel and cobalt is extremely insufficient, leading to a serious problem of rising prices. Therefore, there is a need to develop a low-cost high-energy positive electrode active material.
[0004] Lithium-manganese-rich (LMR) materials are positive electrode active materials with a layered structure that contain an excess amount of lithium and a relatively high manganese content. They exhibit high capacity by applying a new principle called oxygen oxidation-reduction (O-redox) in addition to capacity expression through the oxidation-reduction of existing transition metals. At the same time, they have a high ratio of low-cost manganese, so they are attracting attention as an ultra-low-cost next-generation positive electrode active material.
[0005] However, in LMR materials, the driving force behind high capacity is O-redox, which has low reversibility, so oxygen gas can be released during charging and discharging, which can cause the crystal structure to deteriorate and voltage to drop during the charging and discharging process (voltage decay). In addition, the higher the O-redox capacity in the total capacity, the lower the average discharge voltage of the positive electrode. Therefore, although O-redox is the driving force behind high capacity, if its specific weight is too high, there is a problem that the life characteristics are reduced or the energy density calculated as (capacity x voltage) is reduced. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides a lithium-manganese-rich positive electrode active material with high cost competitiveness, which ensures high capacity characteristics through O-redox and minimizes side effects of O-redox, thereby minimizing voltage drop and energy density reduction and improving life characteristics. [Means for solving the problem]
[0007] In one embodiment, a positive electrode active material for a lithium secondary battery is provided, comprising a compound represented by Chemical Formula 1. [Chemical formula 1] a[Li 1+x (Ni y Mn 1-y ) 1-x O2]+(1-a)[b(LiNi z Mn 1-z O2)+c(Li2MnO3)]
[0008] In the above formula 1, 0 <a<1、0.03≦x≦0.2、0.35≦y≦0.7、0<b<1、0<c<1および0.5≦z≦1である。
[0009] In another embodiment, a positive electrode for a lithium secondary battery is provided that includes the positive electrode active material.
[0010] In another embodiment, a lithium secondary battery is provided that includes the positive electrode, a negative electrode, a separator positioned between the positive electrode and the negative electrode, and an electrolyte.
[0011] In another embodiment, there is provided an all-solid-state secondary battery comprising the positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode. Effect of the Invention
[0012] The positive electrode active material according to an embodiment is a lithium-manganese-rich positive electrode active material, which is highly cost-competitive. By utilizing O-redox, a high capacity can be achieved. At the same time, by controlling the ratio of the O-redox capacity to the total capacity, the problems of voltage drop and energy density reduction can be effectively improved. Therefore, the positive electrode active material exhibits high discharge capacity and average discharge voltage, and can achieve excellent high-temperature life characteristics and high energy density. [Brief description of the drawings]
[0013] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 2] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 3] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Figure 4] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 5] 1 is a graph showing the results of X-ray diffraction analysis (XRD) for the positive electrode active materials of Example 2 (950° C.), Example 5 (700° C.), and Comparative Example 5 (500° C.), showing the peaks of the (003) plane and the peaks of the (020) plane. [Figure 6] 1 is a scanning electron microscope (SEM) image of the particle surface of the positive electrode active material prepared in Example 2. [Figure 7] 1 is a SEM image of the particle surface of the positive electrode active material prepared in Example 5. [Figure 8]1 is a SEM image of the particle surface of the positive electrode active material prepared in Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below so that those skilled in the art can easily implement the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.
[0015] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.
[0016] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.
[0017] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.
[0018] In the drawings, the thickness of layers and regions is exaggerated to clearly show them, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, or plate is said to be "on" another part, this includes not only the case where the part is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" the other part, it means that there is no other part between them.
[0019] Here, the term "layer" includes not only shapes formed on the entire surface when observed in a plan view, but also shapes formed on a portion of the surface.
[0020] The average particle size can be measured by methods well known to those skilled in the art, for example, by using a particle size analyzer, or by using a transmission electron microscope image or a scanning electron microscope image. Alternatively, it can be measured using a dynamic light scattering method, and data analysis can be performed to count the number of particles for each particle size range, and the average particle size can be calculated based on the result. Unless otherwise defined, the average particle size is the diameter (D 50 In addition, unless otherwise defined, the average particle size is the diameter (D) of the particle that occupies 50% of the cumulative volume in the particle size distribution obtained by measuring the size (diameter or major axis length) of 20 or more particles randomly in a scanning electron microscope image. 50 ) may be taken as the average particle size.
[0021] Here, "or" is not to be construed as exclusive; for example, "A or B" is to be construed as including A, B, A+B, etc.
[0022] The term "metal" is understood to include general metals, transition metals, and metalloids (semimetals).
[0023] positive electrode active material In one embodiment, a positive electrode active material for a lithium secondary battery is provided, comprising a compound represented by Chemical Formula 1. [Chemical formula 1] a[Li 1+x (Ni y Mn 1-y ) 1-x O2]+(1-a)[b(LiNi z Mn 1-z O2) + c(Li2MnO3)]
[0024] In the above formula 1, 0 <a<1、0.03≦x≦0.2、0.35≦y≦0.7、0<b<1、0<c<1および0.5≦z≦1.0である。
[0025] In the above formula 1, [Li1+x (Ni y Mn 1-y ) 1-x O2] indicates a solid-solution phase, and [b(LiNi z Mn 1-z It can be said that the compound represented by Formula 1 (Li2MnO2)+c(Li2MnO3) represents a composite phase. In other words, it can be said that the compound represented by Formula 1 includes both a solid solution phase and a composite phase. It can be said that existing lithium-manganese-rich materials generally have either a solid solution structure or a composite structure. On the other hand, it can be said that the positive electrode active material according to an embodiment is a material having not only a composite phase but also a solid solution phase, for example, a material in which a composite and a solid solution are mixed, or a material in which a composite and a solid solution competitively coexist.
[0026] Here, a solid solution can mean a solid mixture in which different elements are mixed completely uniformly, and other elements are mixed and distributed uniformly in the crystals of a solid, like a solution in which a solute is uniformly distributed in a solvent. A solid solution can be a continuum quasi-isostructural compound having new properties due to the strong interrelationship between two or more individual components. The solid solution can be homogeneous, have almost the same composition, and have a single phase or a single crystal structure. In contrast, a complex is made of two or more materials that are combined and have different physical properties, and the materials can be said to maintain a physically distinct state. A complex can be heterogeneous, have two or more compositions, and have two or more phases or crystal structures.
[0027] The presence or absence of a solid solution or a complex can be confirmed through the Energy above Hull analysis described below or XRD diffraction peaks.
[0028] In Chemical Formula 1, it can be said that a is the ratio of the solid solution phase and (1 - a) is the ratio of the composite phase. In Chemical Formula 1, the range of a is 0 < a < 1, and for example, it can be 0.1 ≤ a ≤ 0.9, 0.2 ≤ a ≤ 0.8, or 0.3 ≤ a ≤ 0.7, but the range is not particularly limited.
[0029] In Chemical Formula 1, y is the nickel content of the solid solution phase, and z indicates the nickel content of the layered material in the composite phase. The range of y is 0.35 ≤ y ≤ 0.7, and for example, it can be 0.35 ≤ y ≤ 0.66, 0.4 ≤ y ≤ 0.60, 0.45 ≤ y ≤ 0.55, or 0.5 ≤ y ≤ 0.66, etc. The range of z is 0.5 ≤ z ≤ 1.0, and for example, it can be 0.5 ≤ z ≤ 0.99, 0.5 ≤ z ≤ 0.95, 0.50 ≤ z ≤ 0.85, or 0.6 ≤ z ≤ 0.75, etc.
[0030] The positive electrode active material according to one embodiment can be said to be a lithium - manganese - rich material in which the nickel content is 50 mol% - 70 mol%, or for example 50 mol% - 66 mol% with respect to 100 mol% of the total metal excluding lithium. The positive electrode active material with such a composition excludes or contains a very small amount of expensive cobalt and contains low - cost manganese, thereby ensuring price competitiveness. While ensuring the capacity due to the nickel content, it can also ensure the capacity due to O - redox to achieve a high capacity, and by limiting the O - redox ratio, the problems of voltage drop and energy density reduction can be effectively improved.
[0031] In Chemical Formula 1, x is related to the lithium content, and (1 + x) corresponds to the molar ratio of lithium. The range of x is 0.03 ≤ x ≤ 0.2, and for example, it can be 0.03 ≤ x ≤ 0.15, 0.03 ≤ x ≤ 0.13, 0.03 ≤ x ≤ 0.11, or 0.03 ≤ x ≤ 0.09. For example, the ratio of the lithium content (1 + x) to the content of the total metal excluding lithium (1 - x), that is, (1 + x) / (1 - x) can be 1.06 - 1.5, 1.06 - 1.3, or 1.1 - 1.2.
[0032] In Chemical Formula 1, b and c are each related to the ratios of (LiNi z Mn 1-z O2) and (Li2MnO3) in the composite phase, where 0 < b < 1 and 0 < c < 1. For example, 0.1 ≤ b ≤ 0.9, 0.2 ≤ b ≤ 0.8, or 0.3 ≤ b ≤ 0.7, and 0.1 ≤ c ≤ 0.9, 0.2 ≤ c ≤ 0.8, or 0.3 ≤ c ≤ 0.7, but the range is not particularly limited.
[0033] The cathode active material according to one embodiment may have an "Energy above Hull" of less than 25 meV / atom. "Energy above Hull" means the difference between the Formation energy of the most stable composite phase and the Formation energy of the metastable solid solution phase. 25 meV / atom is the energy that an atom can overcome at room temperature (300K) and indicates the thermodynamic stability of the material at room temperature. It can be said that the larger the "Energy above Hull", the lower the possibility of existing in the solid solution phase and the higher the possibility or ratio of existing in the stable composite phase. The cathode active material according to one embodiment can satisfy the condition that the "Energy above Hull" is less than 25 meV / atom, and thus the composite phase and the solid solution phase can coexist at room temperature.
[0034] Thus, in the cathode active material according to one embodiment containing a solid solution phase, oxygen in the structure can exist relatively stably compared to the existing lithium-manganese-rich composite material. This is because in the existing composite material (a = 0), during the charge-discharge process, LiNi z Mn 1-zIt is known that the lattice constant and lithium concentration of the O2 phase and the Li2MnO3 phase are different, and stress occurs at the interface, which causes oxygen defects. However, in the cathode active material according to an embodiment including a solid solution phase, the amount of the interface is reduced, and the probability of problems occurring at the interface is reduced. Therefore, structural changes due to oxygen defects during charging and discharging are small, and problems of voltage drop due to oxygen generation and structural deterioration can be effectively improved. As a result, in one embodiment, a cathode active material can be provided that uses a lithium-manganese-rich material that has high capacity and is highly cost-competitive, while eliminating the problem of voltage drop due to charging and discharging, improving life characteristics, and improving energy density.
[0035] In the positive electrode active material according to one embodiment, the capacity due to O-redox is exhibited by Li in the solid solution phase. 1+x (Ni y Mn 1-y ) 1-x Li2MnO3 in O2 and / or composite phases. 1+x (Ni y Mn 1-y ) 1-x Either O2 or Li2MnO3, or both, can contribute to O-redox.
[0036] The positive electrode active material according to an embodiment uses O-redox, and can be said to have a composition in which side effects due to O-redox are minimized, and for example, the ratio of the capacity generated by O-redox to the total capacity of the positive electrode active material (100%) can be less than 15%, for example, 1% to 9.9%, or 3% to 9.5%. When the O-redox ratio is controlled to less than 15% in a lithium-manganese-rich material having a Ni content of 50 to 70 mol% as in an embodiment, the problem of voltage drop due to charging and discharging can be effectively improved, and therefore the life characteristics and energy density can be improved.
[0037] An example of a method for measuring the ratio of the capacity generated by O-redox to the total capacity of the positive electrode active material is as follows. A half-cell is manufactured using a positive electrode to which the positive electrode active material is applied and a lithium counter electrode, and a carbonate-based electrolyte is applied, and charging and discharging are performed under the following conditions. After performing the first set, a second set is then performed.
[0038] [1st set] (1) 1st cycle: Charge to 4.65V at 25°C with a constant current of 0.1C, then maintain the voltage until the current value becomes 0.05C, and discharge to 2.5V with a constant current of 0.1C.
[0039] (2) The second cycle: charge to 4.45V at a constant current of 0.2C at 25°C, then maintain the voltage until the current value becomes 0.05C, and then discharge to 2.5V at a constant current of 0.2C.
[0040] [Second set] (1) 1st cycle: Charge to 4.45V at a constant current of 0.2C at 25°C, then maintain the voltage until the current value becomes 0.05C, and then discharge to 2.5V at a constant current of 0.2C.
[0041] (2) The second cycle: charge to 4.45V at a constant current of 0.2C at 25°C, then maintain the voltage until the current value becomes 0.05C, and then discharge to 2.5V at a constant current of 0.2C.
[0042] When the discharge capacity in the second cycle of the first set is X and the discharge capacity in the second cycle of the second set is Y, the value of XY can be said to be the O-redox capacity. When O-redox is activated by charging at 4.65V in the first cycle, the capacity increases in the second cycle, and this increase can be considered as the O-redox capacity. The ratio (%) of the capacity generated by O-redox to the total capacity of the positive electrode active material can be calculated using the following formula 1. [Formula 1] {(XY) / X}×100
[0043] In general, the O-redox reaction is known to occur in a high voltage region of about 4.45V or more in the first cycle of the positive electrode where O-redox occurs, but the voltage at which it is most expressed can be affected by various factors such as the surface state and composition of the positive electrode and the composition of the electrolyte. However, in this high voltage region, side reactions in the electrolyte occur along with the O-redox reaction, and the degree of the side reactions becomes more intense as the voltage increases. If the voltage is increased too much, the ratio of reactions other than O-redox increases, decreasing the accuracy of the O-redox capacity measurement. On the other hand, if the voltage is decreased too much to reduce the electrolyte side reaction, the amount of O-redox reaction itself decreases, which also reduces the accuracy of the O-redox capacity measurement. Therefore, the inventors have set the upper limit voltage of the first cycle of the first set, which can most effectively measure the O-redox capacity, to 4.65V through various experiments. However, this value may vary depending on various factors such as the surface condition and composition of the positive electrode and the composition of the electrolyte, and may be set in the range of 4.55V to 4.8V, for example, 4.55V, 4.6V, 4.7V, 4.75V, 4.8V, etc.
[0044] Generally, the more O-redox is expressed, the lower the average discharge voltage after the activation of O-redox. However, the positive electrode active material according to an embodiment of the present invention can improve the average discharge voltage by controlling the specific gravity of O-redox. For example, the average discharge voltage (vs. Li / Li) in the second cycle of the first set is + ) may be 3.83 V or more, for example, 3.84 V or more. Here, the average discharge voltage may refer to an average discharge voltage in the second cycle of the first set in which a half cell is manufactured using a positive electrode to which the positive electrode active material is applied and the charge / discharge is performed in the first set described above. The average discharge voltage may be calculated, for example, by dividing the integral value of the area under the voltage curve (voltage-capacity graph) by the discharge capacity.
[0045] According to one embodiment, the positive electrode active material is
[0046]
number
[0047] Space group: LiNi z Mn 1-z The ratio of the peak intensity of the (020) plane of the Li2MnO3 phase, which corresponds to the C2 / m space group, to the peak intensity of the (003) plane of the O2 phase (I (020) / I (003) ) may be 2% or less. Here, the (003) plane means a lattice plane corresponding to Miller index (003), and the (020) plane means a lattice plane corresponding to Miller index (020). In XRD, the peak of the (003) plane appears at about 2θ=18-19°, and the peak of the (020) plane appears at about 2θ=20.3-22°. It can be said that the peak of the (020) plane is a peak that appears due to the Li2MnO3 phase in Chemical Formula 1. In the positive electrode active material according to an embodiment, the (020) peak of Li2MnO3 in the composite phase exists, but its intensity is low, and it can be said that the ratio of the peak intensity of the (020) plane to the peak intensity of the (003) plane is controlled to 2% or less. I (020) / I (003) may be, for example, 1.9% or less, 1.8% or less, or 1.0% or less, and may be 0.5 to 2%, 0.8 to 1.9%, 0.3 to 1.8%, or 0.3 to 1.0%. (020) / I (003) When the ratio satisfies the above range, the O-redox density is low, and the problem of voltage drop due to charging and discharging can be improved.
[0048] According to an embodiment, the positive electrode active material may have an a-lattice constant of 2.865 Å or more, for example, 2.870 Å or more, and may be 2.875 Å to 2.885 Å, as determined by XRD. As an example, the a-lattice constant of the positive electrode active material is preferably 2.875 Å or more. In addition, the ratio of the c-lattice constant to the a-lattice constant may be 4.968 or less, for example, 4.965 or less, 4.960 or less, and may be 4.955 to 4.965. When the a-lattice constant of the positive electrode active material and the ratio of the c-lattice constant to the a-lattice constant satisfy the above ranges, the problem of voltage drop during charging and discharging of the lithium secondary battery including the same may be effectively improved, and the life characteristics and energy density may be improved.
[0049] The positive electrode active material according to an embodiment may achieve a higher reversible discharge capacity ratio than existing lithium-manganese-rich materials. Here, the reversible discharge capacity ratio is a method for measuring the ratio of capacity exhibited by O-redox, and may be a value calculated as the ratio (X / A) of the discharge capacity (X) of the second cycle to the charge capacity (A) of the first cycle of the first set. The reversible discharge capacity ratio may affect the N / P ratio, which is the loading level ratio between the negative electrode and the positive electrode in a full cell design. For example, a lower reversible discharge capacity ratio requires a higher loading level of the negative electrode to be inserted into the cell to achieve the same positive electrode capacity, resulting in a decrease in the total energy density. In other words, a higher reversible discharge capacity ratio may be more advantageous in increasing the energy density of a lithium secondary battery.
[0050] According to an embodiment, the positive electrode active material may have a reversible discharge capacity ratio of 63% or more, or 72% or more. The reversible discharge capacity ratio can be further improved by lowering the molar ratio of lithium to all metals excluding lithium, in which case the reversible discharge capacity ratio may be 77% or more, or 79% or more, thereby further improving the energy density of the lithium secondary battery.
[0051] The positive electrode active material according to an embodiment may achieve a higher pellet density than existing lithium-manganese-rich materials. The pellet density of the positive electrode active material may be more than 2.70 g / cc, for example, 2.71 g / cc or more, 2.74 g / cc or more, or 2.71 to 2.85 g / cc. Here, the pellet density refers to the density measured after the positive electrode active material is pressed at 3.3 tons and pelletized. In general, the higher the lithium and manganese content, the higher the specific gravity of LiMnO2, Li2MnO3, etc., which have a low theoretical density in the positive electrode active material, and therefore the pellet density of the positive electrode active material is lower. On the other hand, the positive electrode active material according to an embodiment has a somewhat lower lithium and manganese content than existing lithium-manganese-rich materials, and therefore has a low specific gravity of the phase with a low theoretical density, and therefore is expected to achieve a relatively high pellet density, thereby achieving a high electrode density.
[0052] The positive electrode active material according to one embodiment may have a surface residual lithium content of 0.4 wt% or less, for example, 0.3 wt% or less, 0.2 wt% or less, 0.1 wt% or less, or 0.001 wt% to 0.1 wt%, which is a feature that distinguishes it from high-nickel materials having a nickel content of more than 70 mol%.
[0053] The positive electrode active material may be in the form of secondary particles formed by agglomeration of a plurality of primary particles. 50 For example, the positive electrode active material has an average particle size (D 50 ) is 0.5μm to 8μm, and the average particle size (D 50 Here, the average particle size is determined by measuring the size (e.g., particle size, major axis, or length of major axis) of about 20 random particles in an SEM image of the positive electrode active material, and then obtaining a particle size distribution. The size of the particles that make up 50% of the cumulative volume is defined as the average particle size (D 50 )
[0054] Method for producing positive electrode active material In one embodiment, there is provided a method for producing a positive electrode active material, comprising mixing a precursor represented by Chemical Formula 2 with a lithium source and heat-treating the mixture, wherein the molar ratio of lithium in the lithium source to the total metal of the precursor is designed to be 1.06 to 1.5.
[0055] [Chemical formula 2] Ni y2 Mn 1-y2 (OH)2 In chemical formula 2, 0.5≦y2≦0.7.
[0056] In the formula 2, y2 may be 0.5≦y2≦0.66, 0.5≦y2≦0.60, or 0.5≦y2≦0.55, etc. In other words, the molar content of nickel relative to the total metal in the precursor may be 50 mol% to 70 mol%, for example, 50 mol% to 66 mol%, 50 mol% to 60 mol%, or 50 mol% to 55 mol%.
[0057] By designing the nickel content in the positive electrode active material precursor in this way, it is possible to synthesize a positive electrode active material according to Chemical Formula 1 in which the desired solid solution and complex exist simultaneously. For example, if the nickel content of the precursor relative to the total metal is less than 50 mol% or exceeds 70 mol%, the energy above Hull exceeds 25 meV / atom, making it difficult for the solid solution and complex to coexist at room temperature, and so, for example, only the complex phase may exist. In this case,
[0058]
number
[0059] Space group corresponds to LiNi z Mn 1-z The formation ratio of the Li2MnO3 phase, which corresponds to the C2 / m space group, may be high, and the peak intensity (I b ) versus the (020) peak intensity (I a ), that is, Ia / I b In such a case, the O-redox capacity ratio becomes high, and the voltage drop during charging and discharging becomes large, which may result in a decrease in the life characteristics.
[0060] The molar ratio of lithium in the lithium raw material to the total metal of the precursor (Li / (Ni+Mn)) is 1.06 to 1.5, and may be, for example, 1.06 to 1.4, 1.1 to 1.3, or 1.1 to 1.2. When the molar ratio of lithium satisfies the above range, it is possible to synthesize a positive electrode active material according to Chemical Formula 1 in which a solid solution and a composite exist simultaneously.
[0061] The heat treatment can be carried out in a temperature range of, for example, 700° C. to 1100° C., for example, 700° C. to 1000° C. or 750° C. to 950° C., for 10 to 40 hours, 12 to 36 hours, or 20 to 30 hours.
[0062] The heat treatment may include a temperature increase step, a temperature maintenance step, and a temperature decrease step. The temperature increase rate in the temperature increase step and the temperature decrease rate in the temperature decrease step may be, for example, 1° C. / min to 10° C. / min, or 2° C. / min to 5° C. / min, respectively. When these ranges are satisfied, it is advantageous to effectively synthesize the desired cathode active material represented by Formula 1.
[0063] positive electrode In one embodiment, a positive electrode for a lithium secondary battery is provided, the positive electrode including the positive electrode active material. The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material. The positive electrode active material layer may further include other types of positive electrode active materials in addition to the positive electrode active material, and may optionally further include a binder, a conductive agent, or a combination thereof.
[0064] binder The binder serves to adhere the positive electrode active material particles to each other well and to adhere the positive electrode active material to the current collector well. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.
[0065] Conductive Agent The conductive agent is used to impart electrical conductivity to the electrode, and any electronically conductive material that does not undergo chemical changes in the battery that is constructed can be used. Examples of the conductive agent include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials containing copper, nickel, aluminum, silver, and the like in the form of metal powder or metal fiber; conductive polymers such as polyphenylene derivatives; and mixtures thereof.
[0066] The content of the binder and the conductive agent may be 0.5% by weight to 5% by weight, respectively, relative to 100% by weight of the positive electrode active material layer.
[0067] The positive electrode current collector can be made of Al, but is not limited to this.
[0068] Lithium secondary battery In one embodiment, a lithium secondary battery is provided that includes the above-mentioned positive electrode, negative electrode, and electrolyte. The above-mentioned positive electrode active material is applicable not only to lithium ion batteries but also to all-solid-state secondary batteries. Thus, in one embodiment, a lithium secondary battery is provided that includes a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and an electrolyte, and in another embodiment, an all-solid-state secondary battery is provided that includes the positive electrode, the negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode. Hereinafter, for convenience, the configuration of a lithium ion battery that uses an electrolyte will be described in detail.
[0069] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, and other types according to their shapes. FIGS. 1 to 4 are schematic diagrams showing a lithium secondary battery according to an embodiment, in which FIG. 1 shows a circular type, FIG. 2 shows a square type, and FIGS. 3 and 4 show a pouch type battery. Referring to FIGS. 1 to 4, a lithium secondary battery 100 may include an electrode assembly 40 having a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown). The lithium secondary battery 100 may include a sealing member 60 that seals the case 50 as shown in FIG. 1. Also, the lithium secondary battery 100 in FIG. 2 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. As shown in FIGS. 3 and 4, the lithium secondary battery 100 may include electrode tabs 70, i.e., a positive electrode tab 71 and a negative electrode tab 72, which serve as electrical paths for conducting the current generated in the electrode assembly 40 to the outside.
[0070] negative electrode The negative electrode can include a current collector and a negative electrode active material layer located on the current collector, the negative electrode active material layer including a negative electrode active material and can further include a binder, a conductive agent, or a combination thereof.
[0071] negative electrode active material The negative electrode active material includes a material capable of reversibly inserting / desorbing lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and undoping lithium, or a transition metal oxide.
[0072] Examples of the material capable of reversibly inserting / desorbing the lithium ions include carbon-based negative electrode active materials, which may include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, calcined coke, and the like.
[0073] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.
[0074] As the material capable of doping and undoping lithium, an Si-based negative electrode active material or an Sn-based negative electrode active material can be used. The Si-based negative electrode active material may be silicon, a silicon-carbon composite, SiOx (0 < x < 2), an Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material may be Sn, SnO2, an Sn alloy, or a combination thereof.
[0075] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D 50 ) may be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and the surfaces of the silicon particles coated with amorphous carbon. For example, it may include secondary particles (cores) formed by granulating primary silicon particles, and an amorphous carbon coating layer (shell) located on the surfaces of the secondary particles. The amorphous carbon may also be located between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be present dispersed in an amorphous carbon matrix.
[0076] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0077] When the silicon-carbon composite contains silicon and amorphous carbon, the silicon content may be 10% to 50% by weight and the amorphous carbon content may be 50% to 90% by weight, based on 100% by weight of the silicon-carbon composite. When the composite contains silicon, amorphous carbon and crystalline carbon, the silicon content may be 10% to 50% by weight, the crystalline carbon content may be 10% to 70% by weight, and the amorphous carbon content may be 20% to 40% by weight, based on 100% by weight of the silicon-carbon composite.
[0078] The thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. 50) can be 10 nm to 1 μm, or 10 nm to 200 nm. The silicon particles may exist alone as silicon, or in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon is SiO x (0 < x < 2) can be represented. At this time, the atomic content ratio of Si:O indicating the degree of oxidation can be 99:1 to 33:67. In this specification, unless otherwise defined, the average particle size (D 50 ) means the diameter of the particle with a cumulative volume of 50% by volume in the particle size distribution.
[0079] The Si-based negative electrode active material or the Sn-based negative electrode active material can be used by mixing with a carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material and the carbon-based negative electrode active material are used in combination, the mixing ratio can be 1:99 to 90:10 by weight.
[0080] binder The binder plays a role in making the negative electrode active material particles adhere well to each other and making the negative electrode active material adhere well to the current collector. As the binder, a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof can be used.
[0081] Examples of the non-aqueous binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0082] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0083] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used.
[0084] The dry binder is a polymeric material capable of being fiberized, and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.
[0085] Conductive Agent The conductive agent is used to impart electrical conductivity to the electrode, and any electronically conductive material that does not undergo chemical changes in the battery that is constructed can be used. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and mixtures thereof.
[0086] The content of the negative electrode active material may be 95% to 99.5% by weight relative to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight relative to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive agent.
[0087] Current collector The negative electrode current collector can include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and can be in the form of a foil, sheet, or foam. The thickness of the negative electrode current collector can be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.
[0088] electrolyte The electrolyte for a lithium secondary battery can be, by way of example, an electrolytic solution, which can include a non-aqueous organic solvent and a lithium salt.
[0089] The non-aqueous organic solvent serves as a medium through which the ions involved in the electrochemical reactions of the battery can migrate. The non-aqueous organic solvent may be a carbonate-, ester-, ether-, ketone-, or alcohol-based solvent, an aprotic solvent, or a combination thereof.
[0090] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone solvent include cyclohexanone. Examples of the alcohol solvent include ethyl alcohol and isopropyl alcohol. Examples of the aprotic solvent include nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may contain a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; and sulfolanes.
[0091] The non-aqueous organic solvent may be used alone or in combination of two or more kinds. When two or more kinds are used in combination, the mixing ratio may be appropriately adjusted depending on the desired battery performance, which is widely understood by those working in the field.
[0092] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of 1:1 to 1:9.
[0093] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate solvent and an aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.
[0094] The electrolyte may further contain a vinyl ethyl carbonate, vinylene carbonate or ethylene carbonate based compound to improve the battery life.
[0095] Representative examples of the ethylene carbonate-based compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0096] Lithium salts are substances dissolved in organic solvents and act as a source of lithium ions in the battery to enable basic lithium secondary battery operation and to facilitate the movement of lithium ions between the positive and negative electrodes. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0097] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate ion conductivity and viscosity, and therefore can exhibit excellent performance and allow lithium ions to migrate effectively.
[0098] Separator Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multi-layer film of two or more layers of these may be used, and it is of course possible to use a mixed multi-layer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator.
[0099] The separator may include a porous substrate and a coating layer comprising an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.
[0100] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyether sulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (registered trademark), and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.
[0101] The porous substrate can have a thickness of about 1 μm to 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.
[0102] The organic material may include a (meth)acrylic copolymer including a first structural unit derived from a (meth)acrylamide, and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or a (meth)acrylate, and a structural unit derived from (meth)acrylamidosulfonic acid or a salt thereof.
[0103] The inorganic material may include, but is not limited to, inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. The average particle size (D 50 ) may be 1 nm to 2000 nm, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.
[0104] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.
[0105] The thickness of each of the coating layers may be from 0.5 μm to 20 μm, for example, from 1 μm to 10 μm, or from 1 μm to 5 μm.
[0106] Examples of the present invention and comparative examples are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.
[0107] Example 1 1. Manufacturing of positive electrode active material (1) Preparation of precursor A mixed metal solution was prepared by dissolving nickel sulfate (NiSO4·6H2O) and manganese sulfate (MnSO4·H2O) in distilled water as a solvent to give a molar ratio of Ni:Mn = 50:50. Ammonia water (NH4OH) and sodium hydroxide (NaOH) were prepared as a precipitant to form a complex compound.
[0108] Ammonia water with a concentration of 0.25M was placed in the reactor, and the stirring power was 3.0kW / m 3 The reaction was started by feeding the metal raw material mixed solution and the complexing agent at a rate of 142 ml / min and 34 ml / min, respectively, at a reaction temperature of 50°C. The reaction was carried out for 30 hours while feeding NaOH to maintain the pH. The reaction was terminated when the average size of the obtained particles reached about 10.5 μm. The obtained result was washed and then dried with hot air at about 150°C for 24 hours to obtain nickel-manganese composite hydroxide (Ni 0.5 Mn 0.5 (OH)2) was produced.
[0109] (2) Manufacturing of positive electrode active material Manufactured Ni 0.5 Mn 0.5 (OH)2 and LiOH were mixed so that the molar ratio of Li / (Ni+Mn) was 1.3, and the temperature was increased at a rate of 5°C / min in an oxygen atmosphere, the heat treatment temperature was maintained at 950°C, and then the temperature was cooled to room temperature at a rate of 5°C / min for a total of 24 hours to obtain a positive electrode active material of 0.3[Li 1.13 Ni 0.44 Mn 0.44 O2]+0.7[0.61(LiNi 0.72 Mn 0.28 O2) + 0.26(Li2MnO3)] was produced.
[0110] 2. Manufacturing of lithium secondary batteries (half-cell) 97.7 wt% of the prepared positive electrode active material, 1.2 wt% of polyvinylidene fluoride binder, and 1.1 wt% of carbon nanotube conductive agent were mixed to prepare a positive electrode active material layer slurry, which was then coated on an aluminum foil current collector, dried, and rolled to prepare a positive electrode. At this time, the loading level of the positive electrode active material layer was 10 mg / cm.2 and the density of the final rolled cathode is about 3.5 g / cc.
[0111] A lithium secondary battery was manufactured in a conventional manner using a lithium counter electrode as the negative electrode, a polytetrafluoroethylene separator, 1M LiPF6 dissolved in a solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate mixed in a volume ratio of 2:4:4, and an electrolyte containing 1.5% by weight of vinylene carbonate added.
[0112] Example 2 A positive electrode active material and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 1, except that the molar ratio of Ni and Mn was changed to 66:34 in the preparation of the positive electrode active material precursor. 1.13 Ni 0.57 Mn 0.30 O2]+0.85[0.61(LiNi 0.94 Mn 0.06 O2) + 0.26(Li2MnO3)].
[0113] Example 3 In the preparation of the positive electrode active material, the molar ratio of Li / (Ni+Mn) was changed to 1.2, and the positive electrode active material and the lithium secondary battery were prepared in a substantially similar manner to that of Example 1. The positive electrode active material according to Example 3 had a 0.41[Li 1.09 Ni 0.46 Mn 0.46 O2]+0.59[0.85(LiNi 0.56 Mn 0.44 O2) + 0.10(Li2MnO3)].
[0114] Example 4 In the preparation of the positive electrode active material, the molar ratio of Li / (Ni+Mn) was changed to 1.1, and the positive electrode active material and the lithium secondary battery were prepared in a substantially similar manner to that of Example 1. The positive electrode active material according to Example 4 had a 0.43[Li 1.05 Ni 0.48 Mn 0.48O2]+0.57[0.85(LiNi 0.56 Mn 0.44 O2) + 0.10(Li2MnO3)].
[0115] Comparative Example 1 A positive electrode active material and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 1, except that the molar ratio of Ni and Mn was changed to 34:66 in the preparation of the positive electrode active material precursor. 0.50 Mn 0.50 It can be expressed as Li2MnO3) + 0.34(Li2MnO3).
[0116] Comparative Example 2 A positive electrode active material and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 1, except that the molar ratio of Ni and Mn was changed to 40:60 in the preparation of the positive electrode active material precursor. 0.57 Mn 0.43 It can be expressed as Li2MnO3) + 0.30(Li2MnO3).
[0117] Comparative Example 3 A positive electrode active material and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 1, except that the molar ratio of Ni and Mn was changed to 75:25 in the preparation of the positive electrode active material precursor. The positive electrode active material according to Comparative Example 3 can be expressed as 0.75·LiNiO2+0.25(Li2MnO3).
[0118] Comparative Example 4 A positive electrode active material and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 1, except that the molar ratio of Ni and Mn was changed to 80:20 in the preparation of the positive electrode active material precursor. The positive electrode active material according to Comparative Example 4 can be expressed as 0.80 LiNiO2 + 0.20 (Li2MnO3) + 0.05 Li2O.
[0119] Example 5 A positive electrode active material and a lithium secondary battery were produced in the same manner as in Example 2, except that the heat treatment temperature was changed to 700°C.
[0120] Comparative Example 5 A positive electrode active material and a lithium secondary battery were produced in the same manner as in Example 2, except that the heat treatment temperature was changed to 500°C.
[0121] To facilitate understanding, the design details of the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 to 4 are briefly shown in Table 1 below, the details of Examples 1, 3, and 4 are shown in Table 2 below, and the details of Examples 2 and 5 and Comparative Example 5 are shown in Table 3 below.
[0122] [Table 1]
[0123] [Table 2]
[0124] [Table 3]
[0125] Evaluation example 1: XRD and SEM evaluation X-ray diffraction analysis was performed using a Bruker Powder XRD (D8 Advance) instrument under the following conditions:
[0126] -X-ray wavelength: 1.5406Å (CuKα1) -Slit conditions: Divergence Slit 0.5°, Scattering Slit 0.5°, Receiving Slit 0.20mm -Scan conditions: Continuous Scan, 10°≦2θ≦80°, 0.01° / step, 1.27° / min, total measurement time 55 min XRD analysis was performed on the positive electrode active materials of the examples and comparative examples.
[0127]
number
[0128] Space group corresponds to LiNi z Mn 1-z Peak intensity of the (003) plane of the O2 phase (I b ) for the peak intensity (I a ) ratio is calculated and shown in Tables 1 to 3. a / I b The a-lattice constant (Å) and the ratio of the c-lattice constant to the a-lattice constant were calculated and shown in Tables 1 and 2 as c / a.
[0129] Referring to Tables 1 to 3, the positive electrode active material of the embodiment is I a / I b It can be seen that the ratio of I is 2% or less. In the case of Comparative Examples 1 and 2, where the nickel content is less than 50 mol%, a / I b It is confirmed that the ratio of I exceeds 2%. Referring to Table 2, as the molar ratio of lithium to all metals other than lithium decreases from 1.3 to 1.1, a / I b It can be seen that the ratio of the capacity due to O-redox to the total capacity also decreases, the average discharge voltage increases, and the voltage drop tendency also decreases.
[0130] Meanwhile, XRD analysis graphs for the positive electrode active materials of Examples 2 and 5 and Comparative Example 5 are shown in FIG. 5. In FIG. 5, the horizontal axis represents 2θ(°). The larger graphs represent the peaks in the (003) plane, and the smaller graphs represent the peaks in the (020) plane. Referring to FIG. 5 and Table 3, it can be seen that even if the materials have the same composition, the peak intensity of the (003) plane increases and the peak intensity of the (020) plane decreases as the heat treatment temperature increases during the synthesis process. As a result, the I a / I b6 to 8 are SEM images of the particle surfaces of the positive electrode active materials prepared in Examples 2 and 5 and Comparative Example 5, respectively. It can be seen from FIGS. 6 to 8 that the particle shapes differ depending on the firing temperature.
[0131] Also, in the examples, the a-axis lattice constant is 2.865 Å or more or 2.875 Å or more, and at the same time, the ratio of the c-lattice constant to the a-lattice constant (c / a) is 4.968 or less. On the other hand, in the cases of Comparative Examples 1 and 2, the c / a ratio is greater than 4.968, and in the cases of Comparative Examples 3 and 4, the a-lattice constant is less than 2.865 Å. When the a-axis lattice constant is 2.865 Å or more and the c / a ratio is 4.968 or less as in the examples, it can be confirmed that the ratio of capacity due to O-redox to the total capacity decreases, the average discharge voltage increases, and the tendency for voltage drop is also reduced.
[0132] Evaluation example 2: Pellet density The positive electrode active materials of Examples 1 to 4 and Comparative Examples 1 to 4 were pressed at a pressure of 3.3 tons to form pellets, and the densities were measured. The results are shown in Tables 1 and 2 as P / D (pellet density). Referring to Tables 1 and 2, the pellet densities of the positive electrode active materials of the Examples exceed 2.70 g / cc, and it is possible to realize higher pellet densities than Comparative Examples 1 and 2, which have a high manganese content and a high O-redox ratio. Referring to Table 2, it is possible to see that the pellet density increases as the molar ratio of lithium to the total metals excluding lithium decreases from 1.3 to 1.1. Comparative Examples 3 and 4, which have a low manganese content, show higher pellet densities than the Examples, but it is difficult to realize high capacity because the additional capacity ratio due to O-redox is 0 or less. Therefore, it is understood that the positive electrode active materials of the Examples realize additional capacity due to O-redox and at the same time have a pellet density exceeding 2.70 g / cc, thereby realizing higher electrode density.
[0133] The theoretical densities of LiNiO2, LiMnO2, and Li2MnO3, which are the basic materials of the positive electrode active material, are 4.62 g / cc, 4.04 g / cc, and 3.73 g / cc, respectively, so that the theoretical density of the lithium-manganese-rich material such as the positive electrode active material of one embodiment tends to be lower as the Mn specific gravity is higher and higher as the Ni specific gravity is higher. However, as described above, since O-redox is expressed in Li2MnO3, it can be seen that the high capacity achieved through O-redox has the effect of lowering the theoretical density and offsetting the advantage of increased capacity. From this perspective, the materials of Examples 1 and 2 have a higher theoretical density due to a reduced Mn specific gravity and an increased Ni specific gravity compared to Comparative Examples 1 and 2, which have a high O-redox specific gravity, and a higher theoretical density due to a higher Mn specific gravity compared to Comparative Examples 3 and 4, but a high capacity can be achieved by expressing O-redox, so it can be seen that a strategy of balancing between appropriate O-redox expression and theoretical density has been applied. As described later, as the Li / Me ratio decreases with the same Ni and Mn ratio, the amount of Li2MnO3, an O-redox expression material, decreases, which increases the theoretical density while limiting the O-redox expression. The results of Examples 3 and 4 are consistent with this, and this strategy is another effective method for balancing between adjusting the O-redox capacity and improving the theoretical density.
[0134] Evaluation example 3: Residual lithium The residual lithium content on the surface of the positive electrode active materials of Examples 1 to 4 and Comparative Examples 1 to 4 was measured by HCl titration, and the results are shown in Tables 1 and 2. In the tables, the unit of the residual lithium content is ppm, which is the content relative to 100% by weight of the positive electrode active material, and is 10 -4 The percent by weight is expressed as weight percent. Specifically, 10 g of the positive active material was placed in 100 ml of distilled water and stirred at 300 rpm for 30 minutes, after which HCl was added and the pH change was measured. The unreacted lithium on the surface of the positive active material exists in the form of Li2CO3, LiOH, etc., so CO3 2- , O.H. - Ions include HCl H +The titration is performed by reacting with the nickel. The amount of the HCl solution added was calculated to calculate the amount of unreacted residual lithium. Referring to Tables 1 and 2, the positive electrode active materials of the examples have a residual lithium content of about 0.4 wt% or less, 0.3 wt% or less, or 0.1 wt% or less. On the other hand, in the case of Comparative Example 3 and Comparative Example 4, where the nickel content exceeds 70 mol%, the residual lithium content exceeds 0.4 wt%.
[0135] Evaluation example 4: Evaluation of O-redox capacity The half cells of Examples 1 to 4 and Comparative Examples 1 to 4 were charged and discharged twice in the first set described above, and the discharge capacity (X) of the second cycle was entered as "discharge capacity" in Tables 1 and 2. Separately, the half cells were charged and discharged twice in the second set, and the discharge capacity (Y) of the second cycle was measured. The value obtained by subtracting Y from X is shown as "ΔC" in Tables 1 and 2, which means the capacity due to O-redox. {(XY) / X}×100 was calculated, and the "ΔC / C tot " indicates the ratio of O-redox capacity to the total capacity. Referring to Tables 1 and 2, it can be seen that the O-redox density of the examples is less than 10%. In Table 1, Comparative Examples 1 and 2 show high O-redox density values of 19.6% or more, and Comparative Examples 3 and 4 show no O-redox expression capacity. Referring to Table 2, it can be seen that the O-redox density decreases more as the molar ratio of lithium to all metals excluding lithium decreases from 1.3 to 1.1.
[0136] Evaluation example 5: Evaluation of reversible discharge capacity ratio In the evaluation method of O-redox capacity in Evaluation Example 4, the charge capacity of the first cycle of the first set was divided by the discharge capacity of the second cycle to calculate the reversible discharge capacity ratio, which is shown in Tables 1 and 2. Referring to Table 2, it can be seen that in the case of Examples 3 and 4, in which the molar ratio of lithium to the total metals excluding lithium in the composition of the examples was reduced to 1.2 or less, the reversible discharge capacity ratio was improved to 77% or more, and this shows that it is possible to manufacture using materials optimized for high energy density.
[0137] Evaluation example 6: Evaluation of average discharge voltage The half-cells of Examples 1 to 4 and Comparative Examples 1 to 4 were charged and discharged in a first set, and the average discharge voltage in the second cycle was measured, and the results are shown as "average voltage" in Tables 1 and 2. The average discharge voltage can be calculated by integrating the area under the discharge voltage curve (voltage-capacity graph) obtained after charging and discharging the half-cell, and then dividing the value by the discharge capacity.
[0138] Referring to Tables 1 and 2, it can be seen that the average discharge voltages of Comparative Examples 1 and 2 were below 3.80 V, while the average discharge voltage of the Example was improved to above 3.83 V. Referring to Table 2, it can be seen that the average discharge voltage increases as the molar ratio of lithium to all metals excluding lithium decreases from 1.3 to 1.1.
[0139] Evaluation example 7: Evaluation of life characteristics and voltage drop characteristics After the half-cells of Examples 1 to 4 and Comparative Examples 1 to 4 were charged and discharged twice in the first set, a cycle of charging at 1.0 C and discharging at 1.0 C in the voltage range of 3.0 V to 4.45 V at 45° C. was repeated 50 times or more, and the ratio of the 50th cycle discharge capacity to the initial discharge capacity was calculated and shown in the “high temperature life” in Tables 1 and 2. In addition, the value obtained by subtracting the average discharge voltage at 50th cycle from the average discharge voltage at 1.0 C in the first cycle is shown in the “voltage drop” in Tables 1 and 2.
[0140] Referring to Tables 1 and 2, it can be seen that in the case of Comparative Examples 3 and 4, the life characteristics, i.e., the capacity retention rate at 50 cycles, falls to a level of 71% or less, while the life characteristics of the Example are 77% or more or 94% or more. It can also be seen that in the case of Comparative Examples 1 and 2, the voltage drop is 90mV or more, while in the Example, the voltage drop falls to 70mV or less.
[0141] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention. [Explanation of symbols]
[0142] 100: Lithium secondary battery 10: Positive electrode 11: Positive electrode lead tab 12: Positive terminal 20: Negative electrode 21: Negative electrode lead tab 22: Negative terminal 30: Separator 40: Electrode assembly 50: Case 60: Sealing material 70: Electrode tab 71: Positive electrode tab 72: Negative electrode tab
Claims
1. A positive electrode active material for a lithium secondary battery comprising a compound represented by Chemical Formula 1: [Chemical formula 1] [L) 1+x (N y Mn 1-y ) 1-x O 2 ]+(1-a)[b(L-& z Mn 1-z O 2 )+c(L- 2 MnO 3 )] In Formula 1, 0<a<1, 0.03≦x≦0.2, 0.35≦y≦0.7, 0<b<1, 0<c<1, and 0.5≦z≦1.
0.
2. The positive electrode active material is [Li 1+x (Ni y Mn 1-y ) 1-x O 2 ], and [b(LiNi z Mn 1-z O 2 ) + c(Li 2 MnO 3 2. The positive electrode active material for a lithium secondary battery according to claim 1, comprising all of the composite phases represented by the formula (1) and (2).
3. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein, in Formula 1, 0.5≦y≦0.66 and 0.5≦z≦0.
95.
4. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein x in Formula 1 satisfies 0.03≦x≦0.
15.
5. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein in Formula 1, 0.1≦a≦0.9, 0.1≦b≦0.9, and 0.1≦c≦0.
9.
6. The capacity for the oxidation-reduction of oxygen is Li 1+x (Ni y Mn 1-y ) 1-x O 2 and / or Li 2 MnO 3 The positive electrode active material for a lithium secondary battery according to claim 1 , which is expressed by the formula:
7. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein a ratio of a capacity generated by oxidation-reduction of oxygen to a total capacity of the positive electrode active material is less than 15%.
8. The ratio of the capacity generated by the oxidation-reduction of oxygen to the total capacity of the positive electrode active material (100%) is calculated according to Equation 1. [Formula 1] {(X-Y) / X}×100 In Equation 1, X is the discharge capacity at the second cycle of the first set, and Y is the discharge capacity at the second cycle of the second set. The first and second sets refer to a half cell prepared using a positive electrode to which the positive electrode active material is applied, and charging and discharging are performed under the following conditions. The second set is performed immediately after the first set. [First set] (1) 1st cycle: Charge to 4.65V at 25°C with a constant current of 0.1C, then maintain the voltage until the current value becomes 0.05C, and then discharge to 2.5V with a constant current of 0.1C. (2) The second cycle: charge to 4.45V at a constant current of 0.2C at 25°C, then maintain the voltage until the current value reaches 0.05C, and then discharge to 2.5V at a constant current of 0.2C. [Second set] (1) 1st cycle: Charge to 4.45V at 25°C with a constant current of 0.2C, then maintain the voltage until the current value becomes 0.05C, and then discharge to 2.5V with a constant current of 0.2C. (2) The second cycle: charge to 4.45V at a constant current of 0.2C at 25°C, then maintain the voltage until the current value reaches 0.05C, and then discharge to 2.5V at a constant current of 0.2C.
9. The positive electrode active material for a lithium secondary battery according to claim 8 , wherein an upper limit voltage of the first cycle of the first set is 4.55 V or more and 4.8 V or less.
10. The average discharge voltage of the positive electrode active material is 3.83 V (vs. Li / Li + 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the positive electrode active material is at least 100% by mass.
11. X-ray diffraction analysis [0010] 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein a ratio of a peak intensity of a (020) plane of the C2 / m space group to a peak intensity of a (003) plane of the space group is 2% or less.
12. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the reversible discharge capacity ratio calculated by the following formula 2 is 72% or more: [Formula 2] (X / A) x 100 In Equation 2, A is the charge capacity of the first cycle of the first set, X is the discharge capacity of the second cycle of the first set, and the first set means that a half cell is manufactured using a positive electrode to which the positive electrode active material is applied, and charging and discharging are performed under the following conditions: [First set] (1) 1st cycle: Charge to 4.65V at 25°C with a constant current of 0.1C, then maintain the voltage until the current value becomes 0.05C, and then discharge to 2.5V with a constant current of 0.1C. (2) The second cycle: charge to 4.45V at a constant current of 0.2C at 25°C, then maintain the voltage until the current value reaches 0.05C, and then discharge to 2.5V at a constant current of 0.2C.
13. The positive electrode active material for a lithium secondary battery according to claim 12 , wherein an upper limit voltage of the first cycle of the first set is 4.55 V or more and 4.8 V or less.
14. The positive electrode active material for a lithium secondary battery according to claim 12 , wherein the reversible discharge capacity ratio is 77% or more.
15. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the pellet density of the positive electrode active material is greater than 2.70 g / cc.
16. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the pellet density of the positive electrode active material is 2.71 g / cc to 2.85 g / cc.
17. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the residual lithium content on the surface of the positive electrode active material is 0.4% by weight or less.
18. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the residual lithium content on the surface of the positive electrode active material is 0.1 wt % or less.
19. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the a-lattice constant is 2.865 Å or more as determined by X-ray diffraction analysis.
20. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the a-lattice constant is 2.875 Å or more as determined by X-ray diffraction analysis.
21. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the ratio of the c lattice constant to the a lattice constant is 4.968 or less in an X-ray diffraction analysis.
22. Mixing a precursor represented by Chemical Formula 2 with a lithium source and heat treating the mixture; A method for producing a positive electrode active material, wherein a molar ratio of lithium in the lithium raw material to the total metal of the precursor satisfies 1.06 to 1.5: [Chemical formula 2] Ni y2 Mn 1-y2 (OH) 2 In Chemical Formula 2, 0.5≦y2≦0.
7.
23. The method for producing a positive electrode active material according to claim 22, wherein the heat treatment is carried out at a temperature in the range of 700° C. to 1100° C. for 10 hours to 40 hours.
24. The heat treatment includes a temperature increasing stage, a temperature maintaining stage, and a temperature decreasing stage, The method for producing a positive electrode active material according to claim 22, wherein a temperature increase rate in the temperature increase step and a temperature decrease rate in the temperature decrease step are each 1° C. / min to 10° C. / min.
25. A positive electrode for a lithium secondary battery comprising the positive electrode active material according to any one of claims 1 to 21.
26. The positive electrode according to claim 25 . negative electrode, a separator located between the positive electrode and the negative electrode; and A lithium secondary battery containing an electrolyte.
27. The positive electrode according to claim 25 . a negative electrode, and An all-solid-state secondary battery comprising a solid electrolyte layer located between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Positive electrode for nonaqueous secondary battery, positive electrode active material for nonaqueous secondary battery, nonaqueous secondary battery and on-vehicle nonaqueous secondary battery
JP2015130272A
Positive electrode active material for nonaqueous secondary battery, positive electrode for nonaqueous secondary battery, nonaqueous secondary battery, and on-vehicle nonaqueous secondary battery module
JP2016051504A
Method for manufacturing coated complex oxide particles for positive electrode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery arranged by use of coated complex oxide particles manufactured thereby
JP2016072188A
Nickel-based composite positive electrode active material for lithium secondary battery, manufacturing method thereof, and lithium secondary battery including positive electrode including the same
JP2022000846A
Cathode materials for use in lithium cells and batteries
US20230282820A1